Distinct gelatinous zooplankton communities across a dynamic shelf sea. (13th March 2019) - Haberlin, Damien; Raine, Robin; McAllen, Rob; Doyle, Thomas K.
Abstract: Understanding how gelatinous zooplankton communities are structured by local hydrography and physical forcing has important implications for fisheries and higher trophic predators. Although a large body of research has described how fronts, hydrographic boundaries, and different water masses (e.g., mixed vs. stratified) influence phytoplankton and zooplankton communities, comparatively few studies have investigated their influence on gelatinous zooplankton communities. In July 2015, 49 plankton samples were collected from 50 m depth to the surface, across five transects in the Celtic Sea, of which, four crossed the Celtic Sea Front. Two distinct gelatinous communities were found in this dynamic shelf sea: a cold water community in the cooler mixed water that mainly contained neritic taxa and a warm water community in the warmer stratified water that contained a mixture of neritic and oceanic taxa. The gelatinous biomass was 40% greater in the warm water community (∼ 2 mg C m −3 ) compared with the cold water community (∼ 1.3 mg C m −3 ). The warm water community was dominated by Aglantha digitale, Lizzia blondina, and Nanomia bijuga, whereas the cold water community was dominated by Clytia hemisphaerica and ctenophores. Physonect siphonophores contributed > 36% to the gelatinous biomass in the warm water community, and their widespread distribution suggests they are ecologically more important than previously thought. A distinct oceanic influence was also recorded in the wider warm water zooplankton community, accounting for a ∼ 20 mg C m −3 increase in biomass in that region.